FRAKSINASI AMONIUM SULFAT PADA ENZIM ?-L-ARABINOFURANOSIDASE TERMOSTABIL - I Nengah Wirajana; Ni Nyoman Tri Puspaningsih (Jurnal Kimia (Journal of Chemistry), 2011)
?-L-Arabinofuranosidases (EC 3.2.1.55) catalyze the hydrolysis ?-L-arabinofuranosidic bonds and act synergistically with other hemicellulases enzymes for the complete hydrolysis of hemicelluloses. Yeast Saccharomyces cerevisiae that considered as Generally Recognized As Safe (GRAS) was chosen for expression and secretion of thermostable ?-L-arabinofuranosidase (AbfA) from Geobacillus thermoleovorans IT-08 termofilik dengan teknologi DNA rekombinan. The extracellular enzyme from the secretion result in this recombinant yeast was precipitated with ammonium sulphate fractionation. Base on the result of measurement of the enzyme activity and the concentration of total protein showed that the specific activity of AbfA enzyme was the lowest at 40% saturation of ammonium sulfat, and the highest at 80% saturation of ammonium sulfat.